COMPETITIVE ADVANTAGES OF FOOD TRADE ENTERPRISES AT REGIONAL COMMODITIES MARKETS - L. Kh. Gabidullina (Russian Journal of Economics and Law, 2011)
The article presents the author's hierarchical model for formation of competitive advantages of retail trade enterprises acting at regional commodities markets and develops possible advantages of trade enterprises according to their types.